2009
DOI: 10.1097/sla.0b013e3181bd582b
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection for Transplantable Hepatocellular Carcinoma

Abstract: LR for small solitary HCC in compensated cirrhosis yields an overall survival rate comparable to upfront LT. Despite a significant recurrence rate, close imaging monitoring after resection allows salvage LT in 61% of patients with recurrence on intention to treat analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(83 citation statements)
references
References 43 publications
1
80
1
1
Order By: Relevance
“…Most studies defend anatomic resection as a method to avoid or ameliorate local recurrence [25,26] . Other studies have not been able to confirm this [27] . If the invasive phenotype is minor, as in the case of very early HCC, the spread beyond the segment may be low and anatomic resection may provide a benefit [9] .…”
Section: Liver Resectionmentioning
confidence: 40%
See 1 more Smart Citation
“…Most studies defend anatomic resection as a method to avoid or ameliorate local recurrence [25,26] . Other studies have not been able to confirm this [27] . If the invasive phenotype is minor, as in the case of very early HCC, the spread beyond the segment may be low and anatomic resection may provide a benefit [9] .…”
Section: Liver Resectionmentioning
confidence: 40%
“…In these regards, surgeons may have in mind that patients can be transplanted at the time of recurrence [58] . This strategy of secondary LT is called salvage transplantation [27] . Poon et al [59] published that 80% of patients with recurrence after a LR for HCC remain eligible for LT.…”
Section: Re-resectionmentioning
confidence: 99%
“…Open surgery can provide a proper AR even in more complex disease presentation with a low-risk profile, provided an adequate patient selection [4, 14, 15, 28, 46]. Liver transplantation remains a solution for both the underlying liver cirrhosis and the neoplasm but should be considered upfront only in otherwise untreatable patients (tumor location or compromised liver function) [6-8]. In the patients amenable to resection or ablation, transplantation should be considered a salvage procedure in case of recurrence [6-8].…”
Section: Resultsmentioning
confidence: 99%
“…Authors have even shown that patients who have undergone previous open hepatectomy can enjoy the benefits of a minimally invasive approach [32]. Potential benefits in patients with hepatocellular carcinoma include decreased postoperative ascites, liver failure and lung complications [25,29,33,34]. …”
Section: Discussionmentioning
confidence: 99%